Pengaruh Pengawasan Keuangan Dana Desa Dan Akuntabilitas Pengelolaan Dana Desa Terhadap Kinerja Pemerintah Desa : Efektifitas Pengelolaan Dana Desa Sebagai Variable Mediasi (Studi Empiris Pada Negeri Administratif Gale-Gale Kabupaten Maluku Tengah) - Baiena, La; Hariyanti, Dwi; Usmany, Paul (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to analyze the effect of village fund financial supervision and accountability of village fund management on village government performance mediated by the effectiveness of village fund management. The sample used in this study was 98 respondents. The analysis tool used is Partial Least Square (PLS). The results showed that financial supervision of village funds had no effect on the performance of village governments. Accountability of village fund management affects the performance of village government. The effectiveness of village fund management affects the performance of village government. Financial supervision of village funds affects the effectiveness of village fund management. Accountability of village fund management affects the effectiveness of village fund management. Furthermore, the results of the investigation also show that financial supervision of village funds affects the performance of village governments mediated by the effectiveness of village fund management and accountability of village fund management affects the performance of village governments mediated by the effectiveness of village fund management.